Pengaruh Suhu Terhadap Parameter Fisik Pisang Kepok (Musa acuminata) Selama Penyimpanan - Dimas Triardianto; Adhima Adhamatika; Adi Sucipto (AGROSAINTIFIKA, 2022)
Bananas are the leading fruit commodity with the highest production in Indonesia. Apart from the taste that bananas like, it has excellent nutritional content for humans. One of the varieties of bananas that are often consumed is the kepok banana. Because it is included in the climacteric fruit, kepok bananas undergo a ripening and ripening process after being harvested, this makes their storage period short. Postharvest handling for fruit commodities that is often encountered is cold storage. The purpose of this study was to determine the effect of storage temperature on the quality of the physical parameters of kepok bananas, namely total dissolved solids, weight loss, and hardness during the storage period. The study was designed by storing bananas for twelve days at three different temperatures, namely 15oC, 20oC, and 28oC (room temperature). Storage room temperatures of 15oC and 20oC are carried out in cold storage, while temperatures of 28oC are carried out in room temperature. Storage was carried out for 12 days, by measuring the physical quality of kepok bananas, namely TPT (Total Dissolved Solids) using a refractometer, Weight Loss using digital scales, and Hardness using a pressure test tool on days 3, 6, 9, and 12. The results showed that the storage temperature of 15oC made the rate of change of physical parameters in kepok bananas slower than other temperatures. At the same time, the storage temperature of 28oC made the rate of change of physical parameters in kepok bananas the fastest compared to different temperatures.